Validation of the Malay Version of the Social Functioning Scale (SFS) for Schizophrenia - Shuib, Naniyati; Ahmad, Mahadir; Osman, Zubaidah Jamil; Alwi, Muhammad Najib Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
Social dysfunctions are essential symptom of schizophrenia after cognition which bring a hike in the rates of functional impairment. It is crucial for evaluating the success of treatment although the dimension is still debateable. This study aimed to translate and validate the Malay version of Social Functioning Scale (SFS) which measures social functioning in patients with Schizophrenia. The SFS was translated into Malay language and back translated. This validation study was conducted on 336 healthy and clinical respondents with Schizophrenia from four hospitals in Klang valley, Malaysia who completed for clinical group. The sociodemographic data were collected. Reliability was calculated through Cronbach’s alpha for SFS full scale (α:.80) and all subscales (α: .54 to .89). The SFS has good face and content validity besides the convergent and discriminant validity. Significant bivariate correlation coefficients were found between all subscales and full scale (p